Cyber tournaments and tourism - Medvedev, Dmitriy (Jihočeská univerzita, 2017)
The degree work allowed to not only learn about the cybersport industry as a sport in general, but also bachelor thesis presented the ways how to solve the main problems of the region of České Budějovice: a small number of foreign tourists, acute seasonality, the attention to this area as an intermediate point on the way to the ultimate goal, the lack of tourist attractions, high competition of nearby places and so on. The concept of the tournament described in this paper makes it possible to create for České Budějovice a unique tourist product that will change the perception of what this area can offer, attract new tourists, inform more people about the region and increase the attractiveness of the area as a whole. This work consists of two parts: theoretical and practical. In the theoretical part, the notion of the definition of eSports, the description of basic cybersport disciplines, the history of its appearance and development and its transition from the category of video-games to the category of sports disciplines are given. Also, eSports tournaments and their components have been examined. In the practical part, the target destination was determined, the main tourist problems presented in the Tourism Development Strategies of České Budějovice were studied and a concept of an eSports event was developed, which allows to influence their solutions.
Cyber tournaments and tourism
Keywords: Cybersport; České Budějovice; concept; tournament; cybersport disciplines; target destination; Cybersport; České Budějovice; concept; tournament; cybersport disciplines; target destination